Innovation in Nursing Learning Methods to Improve Students' Critical Thinking - Hardjito S. Darmojo; Partono Siswosuharjo; Fathiyati Fathiyati; M. Adila Rossa (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2025)
Critical thinking is an essential competency that nursing students must possess to support appropriate clinical decision-making and safe nursing practice. However, the application of conventional learning methods remains a challenge in optimally developing critical thinking skills. This study aims to analyze the effectiveness of innovative nursing learning methods in improving students' critical thinking skills. The study used a quasi-experimental design with a pretest–posttest control group approach. The study subjects consisted of 80 undergraduate nursing students divided into an experimental group and a control group. The experimental group received an innovative learning intervention integrating flipped learning, case-based learning, and clinical simulation, while the control group used conventional learning methods. Critical thinking skills were measured using a validated critical thinking instrument. The results showed a significant increase in critical thinking skills in the experimental group compared to the control group (p < 0.001), with a very strong effect size. The highest increase was found in the clinical reasoning aspect. This study concludes that innovative nursing learning methods are effective in improving students' critical thinking skills and are recommended for integration into the nursing education curriculum